Respuesta :

Answer:

[tex]x = -6, x = 4[/tex]

Step-by-step explanation:

Step 1:  Factor

Subtract 24 from both sides

[tex]x^2 + 2x- 24 = 24 - 24[/tex]

[tex]x^2 + 2x - 24 = 0[/tex]

Make two different x's

[tex]x^2 + 2x - 24 = 0[/tex]

[tex]x^2 + 6x - 4x - 24 = 0[/tex]

Make two different parenthesis

[tex]x^2 + 6x - 4x - 24 = 0[/tex]

[tex](x + 6)(x - 4) = 0[/tex]

Step 2:  Solve for x in both equations

[tex]x + 6 = 0[/tex]

[tex]x + 6 - 6 = 0- 6[/tex]

[tex]x = -6[/tex]

[tex]x - 4 = 0[/tex]

[tex]x - 4 + 4 = 0 + 4[/tex]

[tex]x = 4[/tex]

Answer:  [tex]x = -6, x = 4[/tex]

Answer:

C. 4 and -6

Step-by-step explanation: